Modelos de deformación cortical durante la fase intersísmica y su comparación con velocidades GPS para la Zona de Subducción del Perú - Mantilla Calisaya, Eliana Amelia (2018)
In this thesis I have developed forward models of elastic displacement to simulatethe stress accumulation at the plates interface and estimate the surfacedeformation of the earth’s crust during the interseismic phase in the Peruviansubduction zone. The interest in developing this research is due to the fact thatlarge earthquakes occur cyclically and tsunamis in this margin, as demonstratedby the great earthquakes of 1746 (8.6 Mw), 1868 (8.8Mw), 1913 (7.8Mw), 1940(8.1Mw), 1942 (8.1Mw), 1953 (7.6Mw) , 1959 (7.5Mw), 1966 (8.0Mw), 1974(7.9Mw), 1996 (7.7Mw), 2001 (8.4Mw) and 2007 (8.0Mw) and the tsunamiearthquakes of 1960 (7.6Mw) and 1996 (7.5 Mw) occurred in the northern regionof Peru.For modeling I used the elastic displacement theory proposed by Okada (1985),which allows to simulate the process of stress accumulation and deformation fora rectangular fault plane in a homogeneous, isotropic and finite semi-space,based on the model of the Back slip of Savage, (1983). To validate the models,a unified GPS interseismic velocity field has been used and expressed under thesame frame of reference of the research studies carried out during the last 20years in Peru covering the coastal zone, the pre-Andean plain and the westerncordillera, in order to obtain a model of elastic displacement that simulates suchaccumulation of stresses in the plate interface, estimate the area of seismiccoupling and its depth.The results obtained show that for the northern region (lat. 3.0 ° S to 10 ° S) theseismic coupling is between 5 and 13-20 kilometers of depth and induces surfacedisplacements between 0.8 and 8.7 millimeters. . For the central region (lat. 10 °S to 14 ° S) a seismic coupling is estimated between 5 and 33-45 kilometers ofdepth, being deeper comparade to the other regions and induces superficialdisplacements between 1.0 and 46.2 millimeters. The southern region (lat. 14 °S to 19 ° S) is estimated to be a seismic coupling between 5 and 36-43 kilometersof depth and predicts surface displacements between 1.9 and 24.3 millimeters. Ifall the seismic energy accumulated in these fault planes estimated is released ina only seismic event, could occur an earthquake of moderate magnitude (≥7.0Mw) or tsunami earthquakes such as occurred in 1960 and 1996 for thenorthern region, an earthquake of magnitude 8.5Mw for the central region and anearthquake of magnitude 8.0Mw for the southern region.